miR-424-5p reduces ribosomal RNA and protein synthesis in muscle wasting - Kemp,P; Connolly; Paul,R; Farre,Garros R; Natanek; Bloch; Lee,J; lorenzo; Patel,H; Cooper,C; Sayer,A; Wort; et al. (Journal of Cachexia, Sarcopenia and Muscle, 2017)
Background: A loss of muscle mass occurs as a consequence of a range of chronic and acute diseases as well as in older age. This wasting results from an imbalance of protein synthesis and degradation with a reduction in synthesis and resistance to anabolic stimulation often reported features. Ribosomes are required for protein synthesis so changes in the control of ribosome synthesis is a potential contributor to muscle wasting. MicroRNAs (miRNAs) are known regulators of muscle phenotype and have been shown to modulate components of the protein synthetic pathway. One miRNA that is predicted to target a number of components of protein synthetic pathway is miR-424-5p, which is elevated in the quadriceps of patients with chronic obstructive pulmonary disease (COPD).Methods: Targets of miR-424-5p were identified by Ago2 pull-down and the effects of the miRNA on RNA and protein expression were determined by qPCR and western blotting in muscle cells in vitro. Protein synthesis was determined by puromycin incorporation in vitro. The miRNA was over-expressed in the tibialis anterior muscle of mice by electroporation and the effects quantified. Finally, quadriceps expression of the miRNA was determined by qPCR in patients with COPD, intensive care unit acquired weakness (ICUAW), and in patients undergoing aortic surgery as well as in individuals from the Hertfordshire Sarcopenia Study.Results: Pull-down assays showed that miR-424-5p bound to mRNAs encoding proteins associated with muscle protein synthesis. The most highly enriched mRNAs encoded proteins required for the Pol I RNA pre-initiation complex (PIC) required for rRNA transcription, (PolR1A and Upstream binding transcription factor, UBTF). In vitro, miR-424-5p reduced expression of these RNAs, reduced rRNA levels and inhibited protein synthesis. In mice, over-expression of miR-322 (rodent miR-424 orthologue) caused fibre atrophy and reduced UBTF expression and rRNA levels. In humans elevated miR-424-5p as